The Existence and Uniqueness Result for a Relativistic Nonlinear Schrödinger Equation - Yongkuan Cheng; Jun Yang (Abstract and Applied Analysis)
We study the existence and uniqueness of positive solutions for a class of quasilinear elliptic equations. This model has been proposed in the self-channeling of a high-power ultrashort laser in matter.